2010
DOI: 10.1111/j.1523-536x.2010.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Infant Feeding Decision for Socioeconomically Deprived Pregnant Teenagers: The Moral Dimension

Abstract: Breastfeeding was viewed as a morally inappropriate behavior by most of these teenagers, with formula feeding being perceived as the appropriate behavior. Existing breastfeeding promotion activities are likely to continue to fail to reach teenagers experiencing deprivation in England in the absence of effective strategies to change the underlying negative moral norms toward breastfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0
16

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 25 publications
2
69
0
16
Order By: Relevance
“…Giles et al 21 showed that young people have limited exposure to breastfeeding, are unclear about the benefits of breastfeeding and find breastfeeding in public embarrassing. Knowledge about the benefits of breastfeeding increases in pregancy 10,11 but breastfeeding in public continues to be viewed highly negatively 9,22--24 . It appears easier to educate mothers about the benefits of breastfeeding than to alter perceptions of the public acceptability of breastfeeding.…”
Section: Limitations Of This Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Giles et al 21 showed that young people have limited exposure to breastfeeding, are unclear about the benefits of breastfeeding and find breastfeeding in public embarrassing. Knowledge about the benefits of breastfeeding increases in pregancy 10,11 but breastfeeding in public continues to be viewed highly negatively 9,22--24 . It appears easier to educate mothers about the benefits of breastfeeding than to alter perceptions of the public acceptability of breastfeeding.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…There are defined limits on the generalisability of findings from qualitative studies 19 In the UK teenage mothers are among the least likely to breastfeed 1 . Studies have been carried out into the reasons why those from disadvantaged groups do not initiate and continue breastfeeding, many of which are linked to the theory of planned behaviour 10,11,20 . Such studies conclude that family influences and concerns about breastfeeding in public significantly influence infant feeding behaviour 20 and that breastfeeding can be seen as a 'morally inappropriate' behaviour by teenagers 11 .…”
Section: Limitations Of This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Breasts are often seen as sexual objects (Dyson et al, 2010;Guttman & Zimmerman, 2000;Swanson et al, 2005). The Royal College of Midwives commissioned a survey in 1993 exploring men's attitudes towards breastfeeding and found that 50% of men thought that mothers should not breastfeed in public and 14% felt that breastfeeding was unacceptable (RCM, 1993, cited in Dykes & Griffiths, 1998.…”
Section: Introductionmentioning
confidence: 99%